Analisis Laporan Keuangan Sebagai Penilaian Kinerja Keuangan PT.Telekomunikasi Indonesia TBK - Fajar Muttaqin; Fatkhuri Fatkhuri (Epsilon Journal of Management, 2026)
PT Telkom Indonesia (Persero) Tbk (Telkom) is a company that is part of the state-owned enterprises (SOEs) and operates specifically in the field of information technology, communication, and digital telecommunications services in Indonesia. For that reason, financial statement analysis is needed as a source of information about the company's financial condition. Based on the financial reports of PT Telekomunikasi Tbk for the period from 2019 to 2023, there has been a fluctuating increase despite Indonesia being hit by the COVID-19 pandemic in 2020 to 2021. The type of research is quantitative descriptive research with data sourced from the financial reports of PT Telekomunikasi Tbk as of December 31 from 2019 to 2023. The first result, the assessment of the financial performance of PT Telekomunikasi Tbk based on liquidity ratio analysis using the current ratio, shows that the current ratio from 2019 to 2023 has experienced fluctuating conditions but remains in the very good category, above the industry's minimum standard of 200%. Secondly, the results of the solvency ratio analysis using the Debt to Asset ratio (DAR) indicate that the DAR value from 2019 to 2023 is in the very good category, with a value below the industry's maximum standard of 35%. Thirdly, the analysis of profitability ratios using the Return on Equity (ROE) ratio reveals that the ROE value from 2019 to 2023 has experienced fluctuating conditions but remains above the industry standard of 40%.